Thermal Annealing Surface Modification: Effect on Surface and Performance of Electrospun Nylon 6,6 Nanofiber Membrane for Wastewater Treatment - Mohd Asri, Muhammad Amir Nasrin; Abd Halim, Nur Syakinah; Wirzal, Mohd Dzul Hakim; Mohd Yusoff, Abdull Rahim; Bilad, Muhammad Roil (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
As the forefront in fiber materials development, electrospun nanofiber membrane (NFM) is potentially reliable for wastewater treatment due to its excellent properties for instance; large surface area, high porosity, tuneable pore size, and has great flux as compared to other conventional membranes. However, fouling issue will lead to degradation of membrane performance. Fouling issue can be alleviated by applying membrane surface modification. In this study, thermal annealing is applied onto nylon 6,6 nanofiber membrane with three different temperatures (60°C, 80°C and 120°C). Results show that annealing causes membrane shrinkage and reduction of membrane fiber diameter where the fiber reduced from 138.5 nm to 108.5 nm when annealed at 120°C. The optimum annealing temperature for the membrane was found to be at 60˚C as the membrane shows the highest flux at 1200 L/m2.h at 75 minutes filtration time and took longer time to get fouled (>75 minutes) compared with un-annealed membrane (55 minutes). Nylon 6,6 nanofiber membrane is also proven to give more than 90% of COD and turbidity rejection.